Heart Failure Bench to Bedside - Marn̕-Garca̕, Jos.̌ (Contemporary Cardiology, 2010)
Heart Failure (HF) is the final and common pathway of all cardiovascular diseases. Heart Failure: Bench to Bedside helps address a significant need to develop new paradigms and to identify novel therapeutic targets for this pervasive disease. An authoritative contribution to the field, this book provides a detailed description of new findings and emerging methodologies, as well as a critical clinical evaluation of the complex HF syndrome and future therapies. Heart Failure: Bench to Bedside includes a primer on gene profiling and bioenergetics of the normal heart and a discussion of the molecular, genetic, biochemical and cellular techniques critical to understanding HF. Further chapters discuss cardiac remodeling, oxidative stress, and alterations in other organs and systems that are often associated with HF. Heart Failure: Bench to Bedside thoughtfully evaluates current and forthcoming diagnostic techniques and therapies, pharmaceutical and pharmacogenomic-based individualized medicine, gene and cell-based therapies, and the search for new frontiers. Heart Failure: Bench to Bedside presents a clear view of up-to-date approaches to clinical diagnosis and treatment, as well as offering insightful critiques of original and creative scientific thoughts on post-genomic HF research.